Pelatihan Manajemen Laboratorium Berbasis 5R (Ringkas, Rapi, Resik, Rawat, Rajin) Bagi Guru dan Laboran SMKN 1 Cipatujah Tasikmalaya - Handayani, Mustika Nuramalia; Cakrawati, Dewi; Handayani, Sri (Jurnal Pelayanan dan Pengabdian Masyarakat (Pamas), 2025)
The existence of laboratories in schools, especially vocational schools, is very important in increasing students' competence to form professional workers in the industrial world. Teachers and laboratory assistants need to have adequate skills in managing laboratories to optimize learning in schools. Teacher and laboratory assistant at a vocational high school, SMKN 1 Cipatujah Tasikmalaya West Java, especially majoring in agribusiness processing agricultural products has problems, namely limited human resources both in quantity and knowledge and good laboratory management skills. Therefore, laboratory management training is needed for them within the framework of Community Service activities. The aim of this activity is to increase the knowledge and skills of teachers and laboratory assistants in laboratory management, developing a guidebook for laboratory management in vocational high school (SMK). This activity consists of four stages, namely preparation of training materials, socialization of the program to school staff, implementation of training activities and evaluation of activities. The training was carried out well thanks to the support of various parties, the UPI (Universitas Pendidikan Indonesia) academic community and SMKN 1 Cipatujah. Teachers' and laboratory assistants' understanding of the 5R (Seiri–Seiton–Seiso–Seiketsu–Shitsuke) concept and its application in laboratory management has increased. Furthermore, regular assistance or training is needed which can be carried out online.